RETRACTED: G-20 economies and their environmental commitments: Fresh analysis based on energy consumption and economic growth - Li, Puying; Akhter, Mohammad Javeed; Aljarba, Ahmed; Akeel, Hatem; Khoj, Haitham (Frontiers in Environmental Science, 2022)
The impact of economic growth and energy use is still controversial regarding sustainability, and researchers have limited consensus in this regard. Electricity is considered more environmentally friendly compared with direct fossil fuel consumption. However, many developed economies still depend on fossil fuel sources for electricity generation. Therefore, this study attempted to verify the relationship between electricity consumption and carbon emissions in developed economies in the Group of Twenty (G20). Economic growth and foreign direct investment are other important variables for analyzing this relationship. For this purpose, a dataset from 1995–2018 was generated. The study used econometric methods including cross-sectional dependence, cointegration, Fully Modified Ordinary Least Square (FMOLS), Dynamic Ordinary Least Square (DOLS) estimators, and the Pair-wise panel Granger causality test to examine the relationship between dependent and independent variables. The findings show a positive relationship between electricity consumption and CO2 emissions. This indicates that electricity production is still dependent on sources that help increase CO2 emissions in G20 countries. Furthermore, the results show that gross domestic product and its square term confirm the Environmental Kuznets Curve (EKC) theory for these economies. These results suggest that policymakers promote green and clean electricity sources for sustainable economic growth.